The Effect of Tourism Products and Visits on the Economy of Society in Samosir Regency, Indonesia - PASARIBU, Johnson; BADARUDDIN, BADARUDDIN; SANTOSA, Heru; PURWOKO, Agus (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.v10.8(40).22, 2020)
The purpose of this study was to analyze the influence of tourism products and tourist visits on the economy of society. The methods used in this study were descriptive and verification research. Descriptive research is research that aims to obtain a description of the variable characteristics of tourism products and tourist visits to the economy of society. The data analysis method used in testing the hypothesis was path analysis. The results of the study concluded: Tourism Products and Tourism Visits have a positive and significant effect on the economy of society. It is recommended that Samosir regency government, tourism business management and the public to continue to improve tourism products (transportation, accommodation, attractions and entertainment) attract tourist visits instead of relying solely on natural tourism objects, but need renovation and rehabilitation and effective tourism promotion online by the government , private and community towards cultural tourism objects (hobon stone cultural sites, pusuk buhit as the origin of Batak people, ancestral monuments, sigale-gale dances etc.) and religious tourism objects (parmalim belief, legend of the magic of Batak kings) . North Tapanuli Regency Government needs to target tourist visits while fixing tourism products according to tourist demand for the purpose of increasing Tourism Visits in improving the economy of society. Tourism Products and Tourism Visits. It needs guidance on accommodation managers, attraction managers and entertainment so that tourism products offered are competitive in attracting tourist visits because they can improve the people's economy as measured by socio-economic indicators (PAD, PNB, GRDP, per capita income, poverty reduction, HDI improvement, improvement TPAK, TPT, improvement in education and public health levels) in Samosir Regency.